Hand hygiene intricacies in maternity departments in Sub-Saharan Africa: A scoping review. - Ngema, Siyanda A; Mahlangu DW; Mokonyane SB; Makgatho LM; Mokoena SD; Lefentse Vannesa, Magale; Manganye NL; Shongwe AS (Student’s Journal of Health Research Africa, 2026)
Introduction Hand hygiene (HH) is vital in preventing healthcare-associated infections (HAIs), which are a significant concern in maternity departments, particularly in Sub-Saharan Africa (SSA). Despite the critical role of effective HH practices during childbirth, compliance rates remain alarmingly low across the region. This scoping review aims to systematically map the existing research on the intricacies of healthcare workers in maternity departments in Sub-Saharan Africa. Methods Literature published in English across three databases: PubMed, Medline, and ScienceDirect, was reviewed. The methodology involved a comprehensive search strategy that encompassed studies published between January 2016 and May 2025. A robust review process was initiated, led by a team of eight reviewers, who collaboratively assessed the identified literature. To ensure the rigour and thoroughness of the review, the review was supported by a lead reviewer, who oversaw the evaluation process and facilitated consensus on key findings. Results Out of 481 records identified through database searching, only three studies were ultimately selected for inclusion, conducted across multiple SSA countries, with a focus on assessing knowledge, attitudes, and practices regarding HH. The results highlight significant variability in compliance rates, with many facilities reporting suboptimal HH practices due to inadequate resources, training, and awareness. Barriers to effective HH include a lack of supplies, insufficient infrastructure, and cultural attitudes towards HH. Conclusion This scoping review reveals a critical gap in research on hand hygiene practices among healthcare workers in Sub-Saharan African maternity departments, with only three studies meeting the inclusion criteria. These findings underscore an urgent need for expanded research and targeted interventions to improve HH practices and reduce healthcare-associated infections in SSA maternity settings.